The Alawite state in Gorgan and Tabaristan - سليمان صبا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Conciliation. This is what the ruler of Khorasan did when he learned of the peace treaty and that the Muslims had entered Gorgan. Qam and made peace with Suwayd bin Muqrin and the Muslims during When they entered these areas, their condition was not for the inhabitants of the conquered countries to convert to Islam. Rather, they wanted to be open to these populations and deal with them kindly. The Muslims respected the faith of the indigenous people and left them the choice between converting to Islam or remaining in the religion of their ancestors. Perhaps the Muslims wanted this to leave them alone. The indigenous people of the country have the opportunity to think about the new religion so that their entry into Islam is based on conviction and desire and not out of interest or fear.